2010
DOI: 10.2147/tcrm.s9736
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescribing practices by dentists: a review

Abstract: Antibiotics are prescribed by dentists for treatment as well as prevention of infection. Indications for the use of systemic antibiotics in dentistry are limited, since most dental and periodontal diseases are best managed by operative intervention and oral hygiene measures. However, the literature provides evidence of inadequate prescribing practices by dentists, due to a number of factors ranging from inadequate knowledge to social factors. Here we review studies that investigated the pattern of antibiotic u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
251
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(277 citation statements)
references
References 55 publications
6
251
0
5
Order By: Relevance
“…Consequently, pain relief and antibiotic prescription without referral to a dentist was frequently cited as the management strategy. 12,18 Similar to antibiotic prescriptions, prescription of pain relief medications was both a frequently expected (by the patient) and the prescribed treatment option both in the literature 9 and in this study. A significant portion of practitioners in this study (89.2 per cent) reported routinely prescribing pain-relief medication as part of their dental pain management.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Consequently, pain relief and antibiotic prescription without referral to a dentist was frequently cited as the management strategy. 12,18 Similar to antibiotic prescriptions, prescription of pain relief medications was both a frequently expected (by the patient) and the prescribed treatment option both in the literature 9 and in this study. A significant portion of practitioners in this study (89.2 per cent) reported routinely prescribing pain-relief medication as part of their dental pain management.…”
supporting
confidence: 53%
“…This was reflected in a study by Anderson et al who found that patients presenting to medical practitioners are less likely to receive surgical (i.e., dental) intervention and they are more likely to be prescribed antibiotics. 18 Cope et al also found many general medical practitioners considered antibiotics to be the first-line treatment for acute dental-related issues. 9 The trends from medical practitioners in this study show that broad spectrum antibiotics were preferred for treating dental-related problems.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic prescribing may be associated with unfavorable side effects, ranging from gastrointestinal disturbances to fatal anaphylactic shock and development of resistance. (17) Prescribing antibiotics without laboratory validation for its indication promotes multi-drug resistance of microbes which in turn result in using highly potent antibiotics for otherwise mild bacterial infections. (1) In this study, drug usage in the form of injection was found to be 26% that was higher than Patel et al (5.3%) (14) , similar to Adebayo et al (24%) (18) and lower than babalola et al (72.7%).…”
Section: Discussionmentioning
confidence: 99%
“…The prescribing practices of health care professionals are not regulated by the laws, which consider prescribing antibiotics as a role of a trained physician [30]. Unfortunately, laws against the prevention of dispensing unprescribed antibiotics are not enforced in community pharmacies in Jordan [31].…”
Section: Discussionmentioning
confidence: 99%